ChemInform Abstract: Palladium‐Catalyzed Reduction of Carboxylic Acids to Aldehydes with Hydrosilanes in the Presence of Pivalic Anhydride. Issue 17 (28th April 2014) - Fujihara, Tetsuaki; Cong, Cong; Terao, Jun; Tsuji, Yasushi
Abstract A palladium catalyst system that allows the reduction of carboxylic acids to the corresponding aldehydes with hydrosilanes as reducing agent and pivalic anhydride as an indispensable reagent is developed.